Is Non-ideological Education Possible? Didactics from a Constructivist Perspective - Moroz, Jacek (Paedagogia Christiana, 2023)
In this article, I discuss the assumptions of constructivism and how it can influence teaching practices in promoting critical thinking and empowering students to become active and engaged citizens. I emphasise the role and significance of constructivist education in minimising the possibility of shaping students with submissive, uthoritarian and ideologically susceptible personalities. In the article, I argue that constructivism can be a powerful tool for dealing with any manifestation of ideological thinking and promoting a liberal attitude among students, making it an effective strategy for promoting freedom, a deliberative attitude, and critical thinking.